2014
DOI: 10.1371/journal.pone.0106551
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Retinal Vessel Diameters and Fractal Dimensions with Blood Pressure and Cardiovascular Risk Factors

Abstract: BackgroundThis study aimed to investigate the correlation between quantitative retinal vascular parameters such as central retinal arteriolar equivalent (CRAE) and retinal vascular fractal dimension (D(f)), and cardiovascular risk factors in the Chinese Han population residing in the in islands of southeast China.Methodology/Principle FindingsIn this cross-sectional study, fundus photographs were collected and semi-automated analysis software was used to analyze retinal vessel diameters and fractal dimensions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 48 publications
10
42
2
Order By: Relevance
“…21 Most clinical studies measuring Fd have included patients with type 1 diabetes mellitus, 12,13,22À24 patients with increased levels of HbA1c, 25,26 or examined data from patients with diabetes who developed DR over time. 27À29 In a cross-sectional study, Grauslund et al 12 found an independent correlation between lower Fd and the presence of inactive PDR as well as neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Most clinical studies measuring Fd have included patients with type 1 diabetes mellitus, 12,13,22À24 patients with increased levels of HbA1c, 25,26 or examined data from patients with diabetes who developed DR over time. 27À29 In a cross-sectional study, Grauslund et al 12 found an independent correlation between lower Fd and the presence of inactive PDR as well as neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The fractal dimension was the gradient of the logarithm of the number of squares through which the vessel outline passes against the logarithm of the size of the square [7]. Larger values indicated a more complex branching pattern [26]. …”
Section: Methodsmentioning
confidence: 99%
“…It was confirmed that changes sharply in the arch that affect the retinal blood vessels fractal dimensional changes. This is reinforced in research Zhu et al [13], which explains that the fractal dimension associated with blood pressure and cardiovascular risk factors. Blood pressure (hypertension) acute is the major cause hypertensive retinopathy.…”
Section: Results and Analysismentioning
confidence: 80%
“…The study was supported by research conducted Zhu et.al [13]. The study explains that the fractal dimension retinal images have a relationship with blood pressure and central retinal arteriolar equivalent (CRAE) so that the fractal dimension can also be used as an indicator of cardiovascular risk [13].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation